Spike Lee Can Go Straight to Hell! The Cinematic and Religious Masculinity of Tyler Perry. Issue 2 (3rd May 2016) - Neal, Ron
Abstract : This article provides a Black theological reading of the cultural production of African American producer, writer, actor and entrepreneur, Tyler Perry, in conversation with the African American writer, director, producer and polemicist, Spike Lee. In this article I seek to explore issues of masculinity, as addressed through the prisms of cinematic and religious imagery, juxtaposing Perry and Lee and their differing conceptualizations of Black masculinity. In looking at the work of Tyler Perry I hope to explore how Black male identity is played out in terms of religio-cultural tropes within the mainstream culture of America. What I offer in the pages that follow is a reading of Tyler Perry that locates him within a tradition of masculinity in America. What I forward is a historicist interpretation of Black masculinity, which sees Tyler Perry as a gendered throwback from the not too distant past. In light of this reading, I argue that Perry embodies a cultural legacy of African Americans, which has not been fully engaged, a legacy that is worthy of critical examination.